The development of Buddhism in West Malaysia, with special reference to the practice of meditation among young Buddhist / Lau Lee Sing - Lau , Lee Sing (1994)
This thesis concerns the development of Buddhism in West Malaysia, with special reference to meditation among youths. The history of Buddhism in West Malaysia is explained briefly to give the readers some ideas regarding the development of Buddhism in Malaysia. Explanation has also been made regarding the difference between Mahayana and Theravada Buddhism, to provide a more vivid picture of Buddhism in Malaysia. This thesis, as a whole, is divided into five chapters. Chapter I describes the aim of the research, methodology and difficulties faced during the research. Chapter II presents a general discussion of the development of Buddhism in West Malaysia. Chapter III focuses on young Buddhist activities in the country, the practice of meditation among Chinese, especially the undergraduates. A descriptive analysis is on meditation and meditation retreats is included. Chapter IV presents results of a survey. Vipassana meditation and its practice among Chinese youths is discussed in detail. Chapter V gives a conclusion of this study.